2010
DOI: 10.1152/ajpheart.00773.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mechanical efficiency of rat papillary muscle related to degree of hypertrophy of cardiomyocytes

Abstract: Isolated rat papillary muscles of the right ventricle were used to discover the origin of reduced myocardial efficiency in chronic heart failure. Right ventricular hypertrophy was induced by monocrotaline injection, causing pulmonary hypertension. Control (n = 7) and hypertrophied (n = 11) papillary muscles were subjected to sinusoidal length changes at 37 degrees C and 5 Hz with a peak-to-peak amplitude of 15% of the length giving maximum force (L(max)) after being stretched to 92.5% of L(max). Isometric tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
(71 reference statements)
3
28
0
Order By: Relevance
“…Our observation that the RV MAP duration was prolonged is consistent with action potential and QT interval measurements in previous studies (9,26,32). The correlation between the degree of cardiac hypertrophy and APD is a novel observation in this model and is similar to that between impaired mechanical function and hypertrophy recently reported in MCT hearts (40). We also observed prolongation of LV action potentials by MCT, contrary to the findings of Lee et al (26).…”
Section: Discussionsupporting
confidence: 91%
“…Our observation that the RV MAP duration was prolonged is consistent with action potential and QT interval measurements in previous studies (9,26,32). The correlation between the degree of cardiac hypertrophy and APD is a novel observation in this model and is similar to that between impaired mechanical function and hypertrophy recently reported in MCT hearts (40). We also observed prolongation of LV action potentials by MCT, contrary to the findings of Lee et al (26).…”
Section: Discussionsupporting
confidence: 91%
“…The oxygen demand of the right heart can increase threefold due to the increase in pulmonary artery pressure (Handoko et al, 2009) and by a similar factor due to a decrease of mechanical efficiency (Wong et al, 2010). Fig.…”
Section: Oxygen Demand and Supplymentioning
confidence: 99%
“…It is unlikely therefore, that the release of cytochrome c would cause a decrease of VO 2max and PO 2crit in failing myocardium. It is a possibility that mitochondrial damage is the reason for the reduced mechanical efficiency in observed in papillary muscles (Wong et al, 2010). Bache et al (1999) concluded that changes in energy rich phosphate concentrations that occur during high workload of hypertrophic hearts were not due to limited myocardial oxygenation using 1 H nuclear magnetic resonance to monitor myoglobin desaturation in situ in the anaesthetised dog.…”
Section: Oxygen Consumption and Cytochrome C Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In chronic heart failure, myocardial efficiency (cardiac work divided by oxygen consumption) is considerably diminished (Wong et al 2010), which may be due to altered catecholamine handling. van Eif et al (2013) tested the possibility that oxidation of catecholamines in failing hearts is induced by increased monoamine oxidase A (MAO-A) activity within cardiac myocytes and relate to increased number of intrinsic cardiac adrenergic (ICA) cells.…”
mentioning
confidence: 99%